Pasaog SurutTer mloal Klllran Jao Dl Ka bupatcn Sijunjun g Tahun 1994-2013 - Ningsih, Wiwin Sulastri (Pendidikan Sejarah, 2014)
K ilir.1n Jao renninal was opcring at 1994, I)Ccember 24. l11is tescarch is U.<;(.l to telcal lhc preC!nting the S